2016
DOI: 10.1002/jez.2058
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Stress Exposure Generates Higher Early Survival and Smaller Size without Impacting Developmental Rate in a Pacific Salmon

Abstract: Prenatal exposure to elevated glucocorticoids can act as a signal of environmental stress, resulting in modifications to offspring phenotype. While "negative" phenotypic effects (i.e., smaller size, slower growth) are often reported, recent research coupling phenotype with other fitness-related traits has suggested positive impacts of prenatal stress. Using captive Chinook salmon (Oncorhynchus tshawytscha), we treated eggs with biologically relevant cortisol levels-low (300 ng mL ), high (1,000 ng mL ), or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Packed red blood cells were then separated from plasma via centrifugation at 14,000 rpm (13,331 g) and plasma was stored at -80˚C until further analyses. Baseline plasma cortisol was determined using a cortisol enzyme-linked immunosorbent assay (Cayman Chemical, MI, USA) optimized in-house for use in juvenile Chinook salmon (Capelle et al 2016). Samples were run in triplicate across fourteen assay plates at 1:20 dilution.…”
Section: Blood Sampling and Cortisol Assaysmentioning
confidence: 99%
“…Packed red blood cells were then separated from plasma via centrifugation at 14,000 rpm (13,331 g) and plasma was stored at -80˚C until further analyses. Baseline plasma cortisol was determined using a cortisol enzyme-linked immunosorbent assay (Cayman Chemical, MI, USA) optimized in-house for use in juvenile Chinook salmon (Capelle et al 2016). Samples were run in triplicate across fourteen assay plates at 1:20 dilution.…”
Section: Blood Sampling and Cortisol Assaysmentioning
confidence: 99%
“…In Atlantic salmon ( Salmo salar ) where mothers received cortisol injections and eggs were incubated under mild hyperthermia (+2°C), there were no effects on offspring survival (Eriksen, Bakken, Espmark, Braastad, & Salte, ; Eriksen, Espmark, Braastad, Salte, & Bakken, ). However, although under benign environments some studies have reported either lower ( Oncorhynchus mykiss : Li, Bureau, King, & Leatherland, ) and even higher ( O. tshawytscha : Capelle et al, ) early survival for offspring exposed to elevated egg cortisol, the majority of studies have reported no effect across a diversity of fish species ( Danio rerio : Nesan & Vijayan, ; Salmo trutta : Sloman, ; O. kisutch , O. keta , O. nerka : Sopinka et al, ; Sopinka, Hinch, Healy, Harrison, & Patterson, ; O. kisutch : Stratholt, Donaldson, & Liley, ). Considering these contrasting results both within and across fish species, it may not be surprising that exposure to elevated egg cortisol was incapable of ameliorating survival of elevated water temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…After 2 min (when sperm should no longer be motile), we added river water mixed to 1,000 ng/ml concentration of cortisol (H4001; Sigma‐Aldrich Canada Co) dissolved in 90% ethanol (HPLC grade; Sigma‐Aldrich Canada Co) or 0 ng/ml control solution (ethanol and water only) for a 2‐hr incubation. These concentrations and exposure times were chosen as they have been shown in previous published studies to result in biologically relevant elevations of cortisol in the eggs (i.e., within 2 SD of control: Burton, Hoogenboom, Armstrong, Groothuis, & Metcalfe, ; Capelle, Semeniuk, Sopinka, Heath, & Love, ; Sopinka et al, ; Sopinka, Hinch, Healy, Raby, & Patterson, ). After the 2‐hr exposure, we rinsed the eggs using dechlorinated water, and removed three eggs from each cortisol replicate to verify the effectiveness of the cortisol manipulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, nestlings hatching from corticosterone‐injected eggs in our study population were lighter than control nestlings at hatching, but, through compensatory growth, were heavier near the time of nest‐leaving (Strange et al., ), a likely positive effect; however, there are often long‐term costs to compensatory growth (Grace, Froud, Meillère, & Angelier, ; Metcalfe & Monaghan, ; Monaghan, ). There is evidence of positive effects of prenatal corticosterone or cortisol exposure in a variety of taxa (Capelle, Semeniuk, Sopinka, Heath, & Love, ; Meylan & Clobert, ). The immediate cause for these prenatal effects is most likely the maternal corticosterone and other possible compounds associated with elevated maternal corticosterone that were transferred to the eggs.…”
Section: Discussionmentioning
confidence: 99%